Chicken parvovirus and its associations with malabsorption syndrome. (August 2016) - Finkler, F.; Lima, D.A.; Cerva, C.; Moraes, L.B.; Cibulski, S.P.; Teixeira, T.F.; Santos, H.F.; Almeida, L.L.; Roehe, P.M.; Franco, A.C.
Abstract: Malabsorption syndrome (MAS) is a multifactorial syndrome which is characterized by enteric disorders and reduced growth rates of broilers. Such condition is responsible for significant economic losses to the poultry industry. A possible association between chicken parvovirus (ChPV) infections and the occurrence of MAS has been proposed. However, such association has not to date been elucidated in view that ChPV has been detected in healthy as well as in MAS-affected chickens. This study aimed to detect and quantify ChPV loads in sera and tissues of MAS-affected, as well as in healthy broilers. Fifty nine, 39-day-old broilers (50 diseased, 9 healthy birds), obtained from the same flocks, were examined. The highest ChPV DNA loads were detected in MAS-affected broilers, particularly in fecal samples and intestinal tissues ( 5500 genomic copies/300 ng of total DNA). The average viral genome load in serum in MAS-affected birds was 1134 copies/mL, whereas no viral DNA was found in sera and thymus tissues from healthy animals. These findings reveal that MAS-affected broilers consistently carry ChPV DNA is serum, whereas healthy animals do not. In addition, viral loads in tissues (bursa of Fabricius, spleen, intestine and liver) of MAS-affected birds were significantly higher in comparison to the same tissues from healthy broilers. Although preliminary, the results obtained here indicate an association between the detection of ChPV DNA in serum, in addition to high ChPV viral loads in tissues, and the occurrence of MAS in broilers. Further experiments should be performed to confirm such results. Highlights: ChPV viral loads were detected in MAS-affected broilers. ChPV viral loads were elevated in MAS chickens when compared to healthy ones. ChPV loads were higher detected in fecal and intestinal samples.